PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT YAFINDO SUMBER REJEKI DI KOTA BATAM - Camus, Camus; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2019)
This study aims to find out: the influence of promotion partially on consumer satisfaction at PT Yafindo Sumber Rejeki in Batam city, the influence of service quality partially on customer satisfaction at PT Yafindo Sumber Rejeki in Batam city, and the influence of promotion and quality of service simultaneously on customer satisfaction at PT Yafindo Sumber Rejeki in Batam city. The research method used is quantitative research. The population in this study are consumers who shop at PT Yafindo Sumber Rejeki in Batam city. A sample of 204 respondents were taken using accidental sampling technique. The analysis used is descriptive analysis. Data quality test instruments in this study are test data validity and data reliability test. Classic assumption test consists of normality test, heteroscedasticity test and multicollinearity test. The influence test consists of multiple linear analysis and coefficient of determination analysis. In the hypothesis test consists of t test and f test. The results of multiple linear regression analysis show that: promotion affects consumer satisfaction by 39.3% and service quality has an effect on consumer satisfaction by 44.5%, while the results of the coefficient of determination analysis show that promotion and service quality affect customer satisfaction by 56, 8%.